TRANSFORMASI STRUKTUR PERBANKAN INDONESIA: TINJAUAN SISTEMATIS KEBIJAKAN PENGHAPUSAN KBMI 1 DAN ALTERNATIF STRATEGI PENGUATAN MODAL INTI - Adisardjono, Johanes Kuntjoro (ITB AAS Indonesia Surakarta, 2025)
Abstract In late October 2025, Indonesia Financial Services Authority (OJK) issued a directive requiring KBMI 1 banks (core capital IDR 3-6 trillion) to undertake capital strengthening or consolidation, ultimately aiming to eliminate the KBMI 1 category and mandate minimum core capital of IDR 6 trillion. This study employs a Systematic Literature Review (SLR) methodology analyzing 67 academic and practitioner publications to examine policy implications for 34 affected KBMI 1 banks, identify alternative capital strengthening strategies based on international best practices, and evaluate the policy from multi-stakeholder perspectives. Findings indicate that while this transformation presents consolidation opportunities to enhance national banking efficiency and competitiveness, it also introduces significant challenges related to technological capabilities, risk management, integration complexity, and diverse banking business models. The analysis reveals that successful implementation requires balanced approaches that preserve healthy market competition while accommodating bank heterogeneity through differentiated regulatory strategies. Keywords: KBMI 1, banking consolidation, core capital, capital adequacy, financial system stability